A Flavor Lactone Mimicking AHL Quorum-Sensing Signals Exploits the Broad Affinity of the QsdR Regulator to Stimulate Transcription of the Rhodococcal qsd Operon Involved in Quorum-Quenching and Biocontrol Activities - Chane, Andrea; Barbey, Corinne; Bourigault, Yvann; Maillot, Olivier; Rodrigues, Sophie; Bouteiller, Mathilde; Merieau, Annabelle; Konto-Ghiorghi, Yoan; Beury-Cirou, Amélie; Gattin, Richard; Feuilloley, Marc; Laval, Karine; et al. (Frontiers in Microbiology, 2019)
In many Gram-negative bacteria, virulence, and social behavior are controlled by quorum-sensing (QS) systems based on the synthesis and perception of N-acyl homoserine lactones (AHLs). Quorum-quenching (QQ) is currently used to disrupt bacterial communication, as a biocontrol strategy for plant crop protection. In this context, the Gram-positive bacterium Rhodococcus erythropolis uses a catabolic pathway to control the virulence of soft-rot pathogens by degrading their AHL signals. This QS signal degradation pathway requires the expression of the qsd operon, encoding the key enzyme QsdA, an intracellular lactonase that can hydrolyze a wide range of substrates. QsdR, a TetR-like family regulator, represses the expression of the qsd operon. During AHL degradation, this repression is released by the binding of the γ-butyrolactone ring of the pathogen signaling molecules to QsdR. We show here that a lactone designed to mimic quorum signals, γ-caprolactone, can act as an effector ligand of QsdR, triggering the synthesis of qsd operon-encoded enzymes. Interaction between γ-caprolactone and QsdR was demonstrated indirectly, by quantitative RT-PCR, molecular docking and transcriptional fusion approaches, and directly, in an electrophoretic mobility shift assay. This broad-affinity regulatory system demonstrates that preventive or curative quenching therapies could be triggered artificially and/or managed in a sustainable way by the addition of γ-caprolactone, a compound better known as cheap food additive. The biostimulation of QQ activity could therefore be used to counteract the lack of consistency observed in some large-scale biocontrol assays.